Impact of Audit Quality on Tax compliance in Nigeria - Rotimi, Oladele; Dinatu, Nna Alabadan; Adediran, Rasheed Adekunle; Oladele, Taiwo Olabode; Lawal, Adenike Moronke (Annals of Spiru Haret University. Economic Series, 2021)
The study examined the impact of audit quality on tax compliance proxy as tax revenue in Nigeria. Specifically, the study investigated the relationship that exists between auditor independence, engagement performance and tax revenue knowing that many times, tax assessment is based on audited financial statement presented by the firms. Survey research design was adopted using primary data sourced from administration structured questionnaire on the respondents selected from among; the staff of Federal Inland Revenue Service (FIRS), academia (Accountants) and practicing accountants/auditors within Ondo State. The ordinary least square (OLS) model was used to analyze data so collected. The R2 adjusted predictive power of the study was 0.623 (62.3%) and the F-statistic at the 0.01 and 0.05 level of significance which are 4.79 and 3.07 and is less than 6.047 which was a clear indication that, auditor independence and engagement performance have a significant effect on audit quality with resultant effect on tax compliance (tax revenue) in Nigeria. The study therefore recommends that auditors should embrace independence and strictly adhere to established standards and procedures laid down by the government, professional bodies when reporting to enhance audit quality at all times; it is believed this will foster tax revenue generation to argument dwindling revenues.